2015
DOI: 10.3389/fmicb.2015.01230
|View full text |Cite
|
Sign up to set email alerts
|

Heroin inhibits HIV-restriction miRNAs and enhances HIV infection of macrophages

Abstract: Although opioids have been extensively studied for their impact on the immune system, limited information is available about the specific actions of opioids on intracellular antiviral innate immunity against HIV infection. Thus, we investigated whether heroin, one of the most abused drugs, inhibits the expression of intracellular HIV restriction microRNA (miRNA) and facilitates HIV replication in macrophages. Heroin treatment of macrophages enhanced HIV replication, which was associated with the downregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 70 publications
(96 reference statements)
2
20
0
1
Order By: Relevance
“…In our study, we found that methadone treatment of macrophages suppressed the expression of IFN-β and IFN-λ2 ( Figure 3 ). This finding supports the earlier observation that morphine or heroin could significantly inhibit the expression of endogenous IFNs in macrophages ( 49 , 55 ). APOBEC (apolipoprotein B mRNA-editing enzymecatalytic polypeptide-like protein) family members inhibit retroviruses replication by deamination to convert cytidine(C) to uridine (U) of viral DNA ( 56 ), among which APOBEC3F and APOBEC3G can restrict HIV replication in both CD4+ T cells and macrophages ( 57 , 58 ).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found that methadone treatment of macrophages suppressed the expression of IFN-β and IFN-λ2 ( Figure 3 ). This finding supports the earlier observation that morphine or heroin could significantly inhibit the expression of endogenous IFNs in macrophages ( 49 , 55 ). APOBEC (apolipoprotein B mRNA-editing enzymecatalytic polypeptide-like protein) family members inhibit retroviruses replication by deamination to convert cytidine(C) to uridine (U) of viral DNA ( 56 ), among which APOBEC3F and APOBEC3G can restrict HIV replication in both CD4+ T cells and macrophages ( 57 , 58 ).…”
Section: Discussionsupporting
confidence: 93%
“…Studies at the molecular level prove that morphine inhibits the production of several transcription factors and induces miRNAs that inhibit inflammatory reactions. The enhancing effects of heroin on HIV replication processes are based on the heroin inhibition processes of certain miRNAs (specifically, miRNA-28, miRNA-125b, miRNA-150 and miRNA-382) that normally limit the replication of viral particles [ 25 ]. Clinical studies confirm lower levels of several biologically significant miRNAs (in particular, miRNA-582-5p and miRNA-590-5p) in the blood of long-term heroin users [ 26 ].…”
Section: Immunomodulatory Effects Of Opioid Agentsmentioning
confidence: 99%
“…Similarly, endogenous opioid peptides such as β endorphin, endomorphin-1, and dynorphin enhance HIV expression [6467]. Multiple studies have shown that opioid receptor antagonists can reverse the proviral effects of morphine, methadone, heroin, or opioid peptides [44, 59, 61, 62, 64, 65, 6870]. Unfortunately, many drugs of abuse – including synthetic opioids – have not been evaluated thoroughly.…”
Section: Hiv and Substance Abusementioning
confidence: 99%
“…The ability of opioids to modulate epigenetic changes – particularly microRNA expression – highlights another mechanism by which opioids impact viral infection. For example, morphine and heroin inhibit the expression of anti-HIV microRNAs that target the 3’UTR of viral transcripts [59, 61, 70]. Similarly, opioids inhibit anti-HIV microRNAs that stimulate replication of latent HIV in resting CD4 + T cells and monocytes [61, 83].…”
Section: Hiv and Substance Abusementioning
confidence: 99%
See 1 more Smart Citation